Infecção experimental e identificação de uma nova espécie de Spirometra, na região do Pantanal, Brasil - Ana Paula Antunes Nogueira (2024)
Interactions among humans, animals, and environment contribute to the dispersion of pathogens that can infect both humans and animals, leading to the development of zoonoses. This can result in outbreaks and epidemics, causing disturbances to public health and significant economic losses. With globalization and the consequent introduction of new dietary habits, such as the consumption of exotic meats and their often-raw preparation methods, it becomes predictable that contamination of humans by unknown or even unrecorded agents will occur in the near future. Immature forms suggestive of Spirometra sp. were found in reptiles, amphibians, and snakes in the Nhecolândia region of the Pantanal in Southern Mato Grosso, and they required better identification and morphological and molecular characterization. Due to their zoonotic potential, it was imperative to precisely determine this etiological agent and the biological and epidemiological factors involved. This parasite has canids and felids as its definitive hosts and requires two intermediate hosts to complete its life cycle: the first are copepods, where the procercoid develops, and the second are amphibians, reptiles, lizards, and small mammals that ingest the contaminated copepods, in which the plerocercoid or sparganum develops. The predation of these second intermediate hosts by canids or felids completes the cycle by establishing the adult form of Spirometra in the small intestine. However, the ingestion of the intermediate host, which carries sparganum, by other vertebrates that are not its definitive hosts often leads to them becoming paratenic hosts. In humans, sparganosis occurs when ingesting the contaminated second host, contaminated water containing copepods, or using poultices made from tissues with sparganoid forms, thus becoming an accidental host. This zoonotic parasite has a worldwide distribution, with a higher concentration in Asian countries, where it is responsible for serious public health issues. In certain regions, the prevalence in definitive hosts can reach up to 90%. In this study, the species of Spirometra sp. found in the plerocercoid form in amphibians, snakes, and reptiles captured in the Pantanal of Nhecolândia was identified and characterized. Forms of sparganoids recovered from snakes, amphibians, and reptiles captured in the Pantanal were inoculated into four dogs and three cats in an attempt to establish an experimental infection and recover the adult form of the parasite, which is the only form capable of morphologically characterizing the species. After the prepatent period of 13 days, adult forms of Spirometra spp. were recovered from the experimental animals and subsequently characterized morphologically using light and scanning electron microscopy, as well as molecularly by complete sequencing of the cox1 gene and phylogenetic analyses and using the species delimitation methods ABGD, ASAP, GMYC, PTP, and bPTP. The occurrence of a new species of Spirometra sp. in animals from the Pantanal was confirmed. The taxonomic characters used for this genus description are weak and relatively subjective; however, the molecular analysis and the species delimitation methods employed unanimously classified the isolate as a new species of Spirometra. Keywords: Spirometra, zoonosis, sparganosis, integrative taxonomy.